ISRAEL BARU (Interpretasi Kritis atas Teologi Paulus tentang Israel di dalam Roma 9:6-8 dan 11:23-24) - Roy Charly H. P. Sipahutar (Institut Agama Kristen Negeri Tarutung, 2019)
AbstractThis paper is an attempt to critically interpret the text of Romans 9: 6-8 and 11:23-24 which was born because of Paul's struggle with what happened in the Christian community of Rome. Israel is God's covenant people, but on the other hand they have also expressed rejection of the salvation brought by Jesus Christ. The status of the covenant people is being questioned by non-Jews, is it still valid? Paul explained that